Multi-scale shear properties of flax fibre reinforced polyamide 11 biocomposites. (June 2016) - Le Duigou, A.; Bourmaud, A.; Gourier, C.; Baley, C.
Abstract: Multiscale analyses are carried out to evaluate and understand the shear properties and behaviour of a flax fibre reinforced polyamide 11 (PA 11) biocomposite. Tensile tests of [±45] n laminates are performed to evaluate the macroscale in-plane shear properties, while microbond tests are performed to evaluate the apparent interfacial shear strength. Although the shear stiffness of PA 11 biocomposites is lower than the available literature values, the shear strength is higher due to a relatively high interfacial bonding strength. Flax/PA 11 interfacial bonding is controlled by hydrogen bonding rather than adhesive pressure induced by residual thermal stress. A superficial fibre cell-wall layer (primary cell-wall) is observed at different scales, which highlights the contribution of the global structure of flax fibres to the shear properties of biocomposites.